AB1363 Consequences of inflammatory arthritis for productivity loss at work and sick leave: A systematic review. (23rd January 2014) - Lenssinck, M.-L.B.; Burdorf, A.; Boonen, A.; Gignac, M.A.; Hazes, J.M.; Luime, J.J.
Abstract : Background: From onset of IA onwards, the consequences for participation are substantial for the individual patient. Reduced work participation frequently occurs early in the course of the disease.Research in the field of arthritis and employment has focused mainly on permanentwork disability (i.e. arthritis related unemployment, early retirement, or disability pension) and its underlying risk factors (1-4). Objectives: To review research on the occurrence and magnitude of productivity loss at work and sick leave in inflammatory arthritis (IA) patients and to identify its determinants. Methods: PubMed, EMbase, PsycINFO and CINAHL articles to November 2011on IA and productivity loss at work or sick leave were reviewed. Methodological quality was assessed usinga criteria list developed by the authors. Results: Forty-one original studies were identified. Sick leave in IA patients varied from 3.7% in the past four days to 84% in the past 2.5 years. Total duration of sick leave ranged from 0.33 days to 11 days per patient over one month. Six studies reported on 29 different determinants of sick leave of which pain and functional disability were consistently associated. About 17% to 88% of IA patients experienced productivity loss at work. Three studies investigated determinants. Tumor necrosis factor inhibitors (TNFi) were associated with reduced productivity loss at work and sick leave in the trials evaluated. The included studies showed heterogeneity in populations, definitions and measurements of productivity loss at work and sick leave. Conclusions: Early inflammatory arthritis impacts on worker productivity but its estimated magnitude varies. Higher levels of sick leave and productivity loss at work were reported for increased levels of pain and decreased levels of functional ability. TNFi use decreased both sick leave and productivity loss at work. References: Burton W, Morrison A, Maclean R, Ruderman E. Systematic review of studies of productivity loss due to rheumatoid arthritis. Occup Med (Lond) 2006;56(1):18-27. de Croon EM, Sluiter JK, Nijssen TF, Dijkmans BA, Lankhorst GJ, Frings-Dresen MH. Predictive factors of work disability in rheumatoid arthritis: a systematic literature review. Ann Rheum Dis 2004;63(11):1362-7. Detaille SI, Heerkens YF, Engels JA, van der Gulden JW, van Dijk FJ. Common prognostic factors of work disability among employees with a chronic somatic disease: a systematic review of cohort studies. Scand J Work Environ Health 2009;35(4):261-81. Lacaille D. Arthritis and employment research: where are we? Where do we need to go? J Rheumatol Suppl 2005;72:42-5. Disclosure of Interest: None Declared